The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.04.17.20057125
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Critical Illness Pathophysiology Driven by Diffuse Pulmonary Thrombi and Pulmonary Endothelial Dysfunction Responsive to Thrombolysis

Abstract: Critically ill COVID-19 patients have relatively well-preserved lung mechanics despite severe gas exchange abnormalities, a feature not consistent with classical ARDS but more consistent with pulmonary vascular disease. Patients with severe COVID-19 also demonstrate markedly abnormal coagulation, with elevated D-dimers and higher rates of venous thromboembolism. We present four cases of patients with severe COVID-19 pneumonia with severe respiratory failure and shock who demonstrated immediate improvements in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…Similar histopathological findings were noted in the SARS outbreak in Southeast Asia during 2003, which was attributed to a related virus of the coronavirdae family [4]. To date, COVID-19 infection predominantly affects the respiratory system; however, various organ systems have been impacted such as the central nervous system (CNS), kidneys and heart, likely as a sequala of severe inflammation in the setting of microthrombi disease [7,[11][12].…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Similar histopathological findings were noted in the SARS outbreak in Southeast Asia during 2003, which was attributed to a related virus of the coronavirdae family [4]. To date, COVID-19 infection predominantly affects the respiratory system; however, various organ systems have been impacted such as the central nervous system (CNS), kidneys and heart, likely as a sequala of severe inflammation in the setting of microthrombi disease [7,[11][12].…”
Section: Introductionsupporting
confidence: 52%
“…This end stage severe inflammatory response has been categorized as cytokine storm syndrome (CSS). This multi-organ inflammatory process seems to be triggered by the massive intravascular release of pro-inflammatory cytokines such as interleukin-6 (IL-6) into the bloodstream, contributing to prevalence of diffuse endovascular injury, with significant microthrombi burden reported on autopsy series [7][8][9]. This diffuse microthrombi burden combined with endothelial destabilization results in a severe multifocal inflammatory response, noted by the histological presence of megakaryocytes, platelets, fibrin, neutrophils and other inflammatory cells [9].…”
Section: Introductionmentioning
confidence: 99%
“…Dissociation between preserved lung compliance, starkly differing from low compliance typical of ARDS, and severe hypoxemia in critically ill patients with COVID-19 infection prompted questioning of perfusion regulation compromise (15). Later reports also focus on loss of hypoxic vasoconstriction consequent to thrombosis or interstitial edema (17), and autopsy series report platelet-fibrin thrombi disrupting the pulmonary microvasculature (17)(18)(19)(20)(21)(22).…”
Section: E259mentioning
confidence: 99%
“…This double hit affecting the ventilation and perfusion simultaneously underlies the intractable hypoxemia that contributed to the high mortality. None of the animal models replicated the respiratory failure, thromboembolic manifestations, and their The mechanisms of the lung injury and coagulopathy are not well understood, although several known pathways were postulated including cytokine storm leading to upregulation of tissue factor [5,9,24], activation/injury of the endothelium infected by the virus [30,67,71], complement activation [72], alveolar hypoxia promoting thrombosis [73], and autoantibodies against phospholipid and lupus anticoagulant [74,75] modulating the hemostasis and coagulation cascade directly. Hence, the development of animal models that replicate the dysregulation of the inflammation and coagulation could be important, as these would allow the deciphering of the intimate mechanisms at play.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and post-mortem studies of fatal cases of COVID-19 demonstrated major alteration of coagulation and fibrinolysis [17,18]. This was associated with widespread thrombosis of small and large vessels, particularly of the pulmonary circulation contributing to death in a third of patients [8,[28][29][30][31][32][33]. These observations suggest that dysregulated coagulation may be an important mechanism of COVID-19 morbidity and mortality [34].…”
mentioning
confidence: 98%